The custodial Randall-Sundrum model: from precision tests to Higgs physics - Casagrande, Sandro; Goertz, F.; Haisch, U.; Neubert, Matthias; Pfoh, T. (Journal of high energy physics, 2010)
We reexamine the Randall-Sundrum (RS) model with enlarged gauge symmetry SU(2)L× SU(2)R× U(1)X× PLRin the presence of a brane-localized Higgs sector. In contrast to the existing literature, we perform the Kaluza-Klein (KK) decomposition within the mass basis, which avoids the truncation of the KK towers. Expanding the low-energy spectrum as well as the gauge couplings in powers of the Higgs vacuum expectation value, we obtain analytic formulas which allow for a deep understanding of the model-specific protection mechanisms of the T parameter and the left-handed Z-boson couplings. In particular, in the latter case we explain which contributions escape protection and identify them with the irreducible sources of PLRsymmetry breaking. We furthermore show explicitly that no protection mechanism is present in the charged-current sector confirming existing model-independent findings. The main focus of the phenomenological part of our work is a detailed discussion of Higgs-boson couplings and their impact on physics at the CERN Large Hadron Collider. For the first time, a complete one-loop calculation of all relevant Higgs-boson production and decay channels is presented, incorporating the effects stemming from the extended electroweak gauge-boson and fermion sectors.
Gesehen am 25.01.2023